Significance of Contre-Coup Injury in Trauma to Brain for Concluding Manner of Death: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Traumatic brain injury is defined as an alteration in the brain function, or other evidence of brain pathology, caused by an external force. Injuries to brain can be classified as those occurring due to primary damage and secondary damage. Primary damage is that occurs at the time of actual impact. There are multiple types of primary damages that may occur. These include: skull fracture breaking of skull bone, contusion/bruise, hematoma/blood clot, laceration, and nerve damage (diffuse axonal injury). While secondary damage is the damage that occurs over time after the actual brain injury; may include infection, hypoxia (oxygen deprivation), edema (brain swelling), elevated intracranial  pressure, infraction (death of  brain tissue which  results in loss of blood  supply to that region of the brain) and hematoma (focal area of bleeding in the skull due to tearing of blood vessels). When one considers the various types of intracranial lesion produced by trauma to the head, there is one type of injury which excites much speculation as to the application in solving medico legal cases, namely, contre-coup injury a type included in closed head injury. Coup contre-coup injury describes contusions that are both at the site of the impact and on the complete opposite side of the organ. This occurs when the force impacting is not only great enough to cause a contusion at the site of impact, but also is able to move the organ and cause it to slam into the opposite side of the hard protective wall of the organ, which causes the additional contusion. It can be seen in brain, heart[1], spleen and lungs[2,3]. Commonly, it is seen in brain. In most head injuries - notably traffic accidents and falls-there is marked deceleration of the moving head on contact with a fixed surface, though there might still be a ‘coup’ lesion at the site of impact, there is often cortical damage on the opposite side of the brain-the ‘contre-coup’ lesion[4]. Practical points to be considered are - there may be no coup damage at all, only contre-coup. There need be no fracture of skull, even in the presence of severe coup and contrecoup lesions. The most common site for contre-coup injury is in the frontal and temporal lobes. It is often at the tips and on the undersurface of these lobes, and may be symmetrical, if a fall on the occiput has occurred. In temporal or parietal impacts, the contre-coup lesions are on contralateral regions but exact geometrical correspondence is not necessary[5]. Few authors opine that in absence of other injuries to head and brain contre-coup injury is most dangerous. The authors describe here a case where the understanding of coup and contre-coup injury helped in solving the case and administration of justice.
Keywords: Traumatic brain injury; Contre-coup injury; Primary and secondary brain damage; Hematoma; Fracture of skull; Abraded contusion; Traffic accident